Depressive symptoms in Alzheimer's disease: natural course and temporal relation to function and cognitive status. - Holtzer, Roee; Scarmeas, Nikolaos; Wegesin, Domonick J; Albert, Marilyn; Brandt, Jason; Dubois, Bruno; Hadjigeorgiou, George M; Stern, Yaakov (J Am Geriatr Soc, 2005)
OBJECTIVES: To examine the natural course of depressive symptoms in patients with probable Alzheimer's disease (AD), specifically, the temporal relationship between depressive symptoms, function, and cognitive status. DESIGN: Multicenter cohort study with follow-up of up to 14 years. SETTING: Patients from the two Multicenter Study of Predictors of Disease Course in Alzheimer's Disease (Predictors Study) cohorts were recruited at five sites in the United States and Europe. PARTICIPANTS: Patients diagnosed with probable AD (n=536) enrolled in a longitudinal study (Predictors Study). MEASUREMENTS: Depressive symptoms were evaluated at 6-month intervals using the Columbia Scale for Psychopathology in Alzheimer's Disease. The Modified Mini-Mental State (3MS) and Blessed Dementia Rating Scale (BDRS) were used to assess cognitive status and functional activity, respectively. RESULTS: The prevalence of depressive symptoms was stable over the first 3 years of follow-up, at approximately 40%. There was a significant drop to 28% and 24% in the fourth and fifth years of follow-up, respectively. Time-dependent Cox analysis revealed that functional activity (BDRS) but not cognitive status (3MS) was a significant predictor of the first episode of depressive symptoms during follow-up. Generalized estimating equation analyses showed that AD duration and functional activity but not cognitive status were significantly related to depressive symptoms over the entire follow-up period. CONCLUSION: Depressive symptoms are common in AD, but their prevalence decreases over time. Examination of the temporal relationship between depressive symptoms and risk factors suggests that decline in function but not in cognition precedes the first episode of depressive symptoms in patients with probable AD.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognition; Depressive Disorder; Disease Progression; Europe; Female; Humans; Longitudinal Studies; Male; Prevalence; Proportional Hazards Models; United States